2019
DOI: 10.1007/s40003-019-00441-7
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Estimation of Evapotranspiration by Standardizing Parsimonious Method

Abstract: Evapotranspiration (ET) is one of the important components of the hydrological cycle which is essential for sustainable water resource management and ecohydrological studies. Accurate estimation of ET is a crucial task in datascarce regions due to limited meteorological variables. There exist a number of indirect methods among which the standard method for computing ET is FAO-56-Penman-Monteith (PM) method. However, due to paucity of flux data such as the components of net radiation, relative humidity, vapour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…In a recent study by Khosravi et al (2019) have compared the different methods based on the kernel and standalone tree based algorithms and found that the prediction power of kernel based functions are higher than non-kernel based functions. The findings of the study are corroborated with our results and support firmly the results with the error measures and graphical indicators obtained through model simulations (Kumari and Srivastava, 2020;Elbeltagi et al, 2021). Sattari et al, 2021 showed that poly kernel function provides the better results than the RBF kernel also they found that different scenarios yielded the same results of poly kernel functions.…”
Section: Evaluation Of Different Models Using Statistical Indicatorssupporting
confidence: 90%
“…In a recent study by Khosravi et al (2019) have compared the different methods based on the kernel and standalone tree based algorithms and found that the prediction power of kernel based functions are higher than non-kernel based functions. The findings of the study are corroborated with our results and support firmly the results with the error measures and graphical indicators obtained through model simulations (Kumari and Srivastava, 2020;Elbeltagi et al, 2021). Sattari et al, 2021 showed that poly kernel function provides the better results than the RBF kernel also they found that different scenarios yielded the same results of poly kernel functions.…”
Section: Evaluation Of Different Models Using Statistical Indicatorssupporting
confidence: 90%
“…These constants limit the model to specific sites and can engender overestimations of ET rates which in turn can lead to excess irrigation. Hence, several studies investigated the validity of the Hargreaves model under various locations and suggested calibration parameters, which helped in reducing the overestimation of ET values [53]. For example, a calibration conducted by [54] decreased the overestimation of ET by 16.3%.…”
Section: Hargreaves and Samani Modelmentioning
confidence: 99%
“…In recent decades, our understanding of vegetation modeling, water resource management, and hydrological and environmental evaluation has improved thanks to remote sensing-based vegetation indices [ 23 ]. Over the years, other datasets such as MeteoSat, MODIS and Landsat series were used for similar purposes at a variety of temporal and spatial scales [ 24 ].…”
Section: Introductionmentioning
confidence: 99%